Medicines of the soul : female bodies and sacred geographies in a transnational Islam - Malti-Douglas, Fedwa (University of California Press, 2001)
In this work, the autobiographical writings of three leading women in today's Islamic revival movement reveal dramatic stories of religious transformation.